Growth parameter of oil palm (Elaeis guineesis jacq.) seedlings in response to fertilizer type in Felcra Bukit Pedoman, Mersing / Mohd Hafiz Hamzi N.R.Azmee - N.R.Azmee, Mohd Hafiz Hamzi (Faculty of Plantation and Agrotechnology, 2019)
Oil palm (Elaeis guineensis) is a subtropical plant that is originated from West Africa which comes from Arecaceae family. Using better fertilizer in early development of oil palm seedling is an important thing to enhance the crop growth. This case study is conducted to determine which type of fertilizers will give higher growth rate on the oil palm seedlings. The variety of D×P Yangambi was used with the age of 2 months of seedling. There are three type of treatment with five replication which for treatment 1 control (compound NPK fertilizer 15/15/15), treatment 2 mix NPK with organic fertilizer and treatment 3 organic fertilizer (8/8/8 + organic humus). This experiment is carried out by using Complete Randomized Design (CRD) for 60 days with 6 times of data collection per 10 days. The results from the experiment show that there is no much different on the growth rate of the seedlings among the three treatments but organic fertilizer show the highest growth. Supported by SPSS analysis result, the data was not normally distribute (P < 0.05) by using the One-Way ANOVA Test result showed that the plant height, leaf width and leaf height were not significant among the three treatment (P > 0.05). However, the stem diameter and the dry weight of the NPK T1 and organic T3 was significant compare to mix fertilizer T3 treatments (P < 0.05).